Barley Resistance to Fusarium graminearum Infections: From Transcriptomics to Field with Food Safety Concerns - Hameed, Amir; Poznanski, Pawel; Noman, Muhammad; Ahmed, Temoor; Iqbal, Adnan; Nadolska-Orczyk, Anna; Orczyk, Wacław (Journal of agricultural and food chemistry, 2022)
Global climate change and the urgency to transform food crops require substantial breeding efforts to meet the food security challenges. Barley, an important cereal, has remained a preferential host of phytotoxic diseases caused by the Fusarium graminearum that not only severely reduces the crop yield but also compromises its food quality due to the accumulation of mycotoxins. To develop resistance against Fusarium infections, a better understanding of the host–pathogen interaction is inevitable and could be tracked through molecular insights. Here, we focused precisely on the potential gene targets that are exclusive to this devastating pathosystem and could be harnessed for fast breeding of barley. We also discuss the eco-friendly applications of nanobio hybrid and the CRISPR technology for barley protection. This review covers the critical information gaps within the subject and may be useful for the sustainable improvement of barley from the perspective of food and environmental safety concerns.